1983
DOI: 10.1056/nejm198305123081901
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Sensitivity to Collagen in Thromboangiitis Obliterans

Abstract: We studied 39 patients with thromboangiitis obliterans to determine their cellular and humoral immune responses to native human collagen Type I and Type III, which are constituents of blood vessels. Cell-mediated sensitivity to these collagens was measured by an antigen-sensitive thymidine-incorporation assay. The mean stimulation index--the ratio of thymidine incorporation in the presence of antigen to that in its absence--with both Type I and Type III collagens used as antigens was significantly higher in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
4

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(64 citation statements)
references
References 10 publications
3
56
0
4
Order By: Relevance
“…Complete abstinence from tobacco use (including pipe smoking and tobacco chewing) will halt disease progression (5). More recently, investigators have shown that patients with TAO have an increased cellular immune response to collagen types I and III, which are normal constituents of blood vessels (11). This type of autoimmune phenomenon has been supported further by the presence of anticollagen antibodies in some patients with Buerger's disease (11).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Complete abstinence from tobacco use (including pipe smoking and tobacco chewing) will halt disease progression (5). More recently, investigators have shown that patients with TAO have an increased cellular immune response to collagen types I and III, which are normal constituents of blood vessels (11). This type of autoimmune phenomenon has been supported further by the presence of anticollagen antibodies in some patients with Buerger's disease (11).…”
Section: Discussionmentioning
confidence: 92%
“…More recently, investigators have shown that patients with TAO have an increased cellular immune response to collagen types I and III, which are normal constituents of blood vessels (11). This type of autoimmune phenomenon has been supported further by the presence of anticollagen antibodies in some patients with Buerger's disease (11). Furthermore, certain human leukocyte antigens (HLA) (types A9, B5, and DR4) have been reported to occur in a greater-than-expected frequency in patients with TAO, suggesting a possible genetic predisposition to this disease (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Use or exposure to tobacco plays central role in the initiation and progression of the disease. By using an antigen-sensitive thymidine-incorporation assay, Adar et al [20] showed that patients with TAO have an increased cellular sensitivity to type I and III collagen, compared to that in patients with arteriosclerosis obliterans or healthy males. De Moerloose et al [21] found a marked decrease in frequency of the HLA-B12 antigen in patients with Buerger's disease (2.2% vs. 28% in controls).…”
Section: Etiologymentioning
confidence: 99%
“…Various studies were undertaken to examine the mechanism of the immune injury. An increased cellular and humoral response to collagen [28,29], circulating immune complexes [30,31], elevated antielastin titers [32] and abnormal elastin degradation [33] were reported. The altered production of IL-6, IL-12 and IL-10, the increased apoptosis as well as the elevated levels of circulating immune complexes were proposed to be the reason for the persisting immune inflammation in TAO [34].…”
Section: Introductionmentioning
confidence: 99%